The Study of Language Used in Indonesian Local News: Pojok Kampung JTV - Nindya Yunita Ardyani (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
Pojok Kampung is a news program based on the second largest city in Indonesia, named Surabaya in East Java. Unlike any other news programs in Indonesia, Pojok Kampung uses Javanese-Surabaya dialect, not Indonesian, to deliver its content which gains a lot of controversies. The paper presents some issues related to: The Javanese-Surabaya dialect and the chosen words used in Pojok Kampung program, the inappropriate words in the program, and what Indonesian especially the citizen of Surabaya’s opinion about Pojok Kampung. To address them, a mixed-methods was applied, a mixed between qualitative and quantitative methods at the level of descriptive analysis. Observation to Pojok Kampung’s broadcasting and interview to some students of English Department of State University of Surabaya were conducted, and questionnaires to the citizen of Surabaya and outside of Surabaya were distributed through Google Form. The result indicates that Pojok Kampung has used a lot of vulgar and inappropriate words, according to the citizen. However, some citizen said that Pojok Kampung has given a whole new information and more extensive knowledge to Javanese dialect, as well as helping a local language to preserve. Pojok Kampung itself is claimed that it uses the correct Javanese-Surabaya dialect, in fact, some people do not agree regarding this matter. The finding may indicate that some inappropriate words in Pojok Kampung program are not even commonly used by the citizen of Surabaya. In their opinion, Pojok Kampung’s dialect does not represent a proper Javanese-Surabaya dialect at all